Managing the purchase of information systems technology: guidelines for success. - Wyde, Richard (Public Welfare)
The writer provides 15 guidelines for health and human service agencies to follow when purchasing information technology systems or services. The guidelines suggest ways for agencies to avoid pitfalls along the way and also give remedies for problems that may occur. Agencies that adhere to these guidelines have a much higher chance of success with their projects than those that do not. Before committing to the purchase of new technology, agencies should obtain all possible protections, being sure to describe and detail them clearly in the contract, thus providing them with a method of recourse if the system fails.